The Meaning of Industrial Revolution 5.0 For The Accountant Profession - Hidayatin, Dina Alafi; Amrina, Hafidza Nash'ul; Wahyudi, Iwan (The Journal of Financial, Accounting, and Economics, 2024)
The Industrial Revolution 5.0 is marked by rapid digital involvement and the dominance of robotics and artificial intelligence in all areas of business life. This condition requires people to be able to adapt by creating innovation and self-development. Even though it broadly has a positive impact on human life, on the other hand, if it is not controlled properly it will cause unrest. The accounting profession is one of the parties that will be negatively impacted by this condition. Through this research, the researcher wants to convey how an accountant should interpret the era of the Industrial Revolution 5.0. The results obtained from this research conclude that a professional accountant must be able to control himself by opening his mindset in dealing with it. Through optimistic thinking, a professional accountant can bring himself to think more about solutions rather than just raising concerns. There are many ways that an accountant can do to maintain its existence. Accountants can invest in developing skills and knowledge in the field of digital technology, opening themselves up to being able to live side by side with technology to support their work, and mastering certain skills that are in line with current developments.